(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
In modern social conditions, it is of particular relevance the problem of the formation of general cultural competencies and its important component - social and humanitarian competence as an integral quality of training specialists for professional activities in the legal field.